Hydrocarbons in the ecosystem of the White Sea. - Nemirovskaya, Inna A (PANGAEA, 2005)
Data are presented on concentration and composition of aliphatic and polycyclic aromatic hydrocarbons (HC) in water, suspended matter (collected with a Juday net and by a separator), and in bottom sediments of the White Sea. It was found that during the last years the level of aliphatic HC concentrations in waters of the White Sea (aver. 18 µg/l) practically did not change and was comparable with average concentrations in shelf areas of the World Ocean. In water and bottom sediments distribution of HC is determined by discharge of river marginal filters. Here sedimentation of the bulk of anthropogenic HC occurs. That is why a grain-size controlling factor is not active in the zone of the river depocenter (in particular, of the North Dvina River). The same reasons most probably may explain differences in degree of geochemical relationships between contents of TOC and HC in suspended matter and bottom sediments. After passing through marginal filters natural HC are dominant in all migration forms.
Hydrocarbons in water, suspended matter, and bottom sediments of the White Sea
Keywords: Archive of Ocean Data; ARCOD; JUDAY; Juday net; MULT; Professor Shtokman; PSh55; PSh55-1S; PSh55-2S; PSh55-3S; PSh55-4911; PSh55-4912; PSh55-4913; PSh55-4914; Psh55-4918; Psh55-4920; PSh55-4923; PSh55-4924; PSh55-4925; PSh55-4926; PSh55-4927; PSh55-4928; PSh55-4929; PSh55-4930; PSh55-4931; PSh55-4932; PSh55-4933; PSh55-4934; PSh55-4935; PSh55-4936; PSh55-4937; PSh55-4938; PSh55-4939; Psh55-4940; Psh55-4941; PSh55-4S; PSh55-5S; SEPAR; Separator; White Sea